Perceptions of healthcare finance and system quality among Nigerian healthcare workers. - Blessing Osagumwendia Josiah; Emmanuel Chukwunwike Enebeli; Brontie Albertha Duncan; Lordsfavour Uzoma Anukam; Oluwadamilare Akingbade; France Ncube; Chinelo Cleopatra Josiah; Eric Kelechi Alimele; Ndidi Louis Otoboyor; Oghosa Gabriel Josiah; Jemima Ufuoma Mukoro; Blessing Chiamaka Nganwuchu; et al. (Public Library of Science (PLoS), 2024)
Nigeria's healthcare system faces significant challenges in financing and quality, impacting the delivery of services to its growing population. This study investigates healthcare workers' perceptions of these challenges and their implications for healthcare policy and practice. A cross-sectional survey was conducted with 600 healthcare professionals from eight states across Nigeria, representing a variety of healthcare occupations. Participants completed a questionnaire that assessed their perceptions of healthcare financing, quality of care, job satisfaction, and motivation using a 5-point Likert scale, closed- and open-ended questions. Descriptive statistics, Chi-squared test, and regression analysis were used to analyze the data. The findings revealed that healthcare workers were generally not satisfied with the current state of healthcare financing and system quality in Nigeria. Poor funding, inadequate infrastructure, insufficient staffing, and limited access to essential resources were identified as major challenges. These challenges contributed to low job satisfaction, demotivation, and a desire to leave the profession. Socioeconomic factors, location State of practice, professional designation (clinical vs nonclinical), clinical designation (profession), and employment type (full-time vs part-time) were found to influence healthcare workers' perceptions (p < 0.05). The findings indicated a need to improve healthcare workers' satisfaction and retention, and quality of care in Nigeria, by increasing healthcare funding, transparent fund management protocols, investing in infrastructure and human resource development, and addressing regional healthcare disparities. By implementing these reforms, Nigeria can enhance the quality and accessibility of healthcare services and improve the health and well-being of its citizens.